Molecular Docking of Broad-Spectrum Antibodies on Hemagglutinins of Influenza A Virus. (September 2019) - Le, Khanh PB; Do, Phuc-Chau; Amaro, Rommie E; Le, Ly
Influenza A has caused several deadly pandemics throughout human history. The virus is often resistant to developed treatments because of its genetic drift or shift property. Broad-spectrum antibodies show a promising potential to overcome the resistance of influenza viruses. In silico studies on broad-reactive antibodies and their interactions with hemagglutinins might shed light on the rational design of a universal vaccine. In this study, 11 broad-spectrum antibodies (or antigen-binding fragments) and 14 hemagglutinins of H3N2 and H5N1 strains were docked and analyzed to provide information about the construction of the scaffold for using universal antibodies against the influenza A virus. Antigen-binding fragments that have high number of appearances in the top 3 within each H3 and H5 subtypes were chosen for protein-protein interaction analysis. The results show that while the hydrogen bond is important for Ab/Fab binding to H3, the H5-Ab/Fab system may need cation-pi interaction for a strong interaction.